Polish struggle with modernity - Mazur, Krzysztof (Journal of Public Governance, 2018)
The main thesis of the paper is that a redefinition of the Polish national identity could be a crucial factor in the process of seeking a way out of the contemporary economic crisis. First, on the basis of works by Pitirim Sorokin (Sorokin 1957) and Niklas Luhmann (Luhmann 2007), the author argues that the contemporary economic crisis is deeply rooted in culture. In the second part this general ref lection leads to an analysis of the materialistic paradigm in social sciences, which limited the ref lection on the human being to his or her financial preferences (Grassl 2012). As a result of such a domination of the materialistic paradigm, the economic way of thinking dominates over our cultural life. The third part offers a project of redefinition of the paradigm which shows that to avoid objectifying human beings, we need to establish a primacy of moral values on the free market (Kędzierski 2012). National identity has to play a key role in this process because it bounds culture, society, and the state. Therefore, in the fourth part of the paper the author presents an integral theory of the nation (Łuczewski 2012). In the fifth part he describes the evolution of Polish identity which leads him to the conclusion that contemporary Polish identity is at a turning point. It should now be modified (Skrzypulec 2013) because its present form has entered the phase of primordiality,which makes it useless in the era of globalization. Therefore, in the last part of the paper, the author proposes five formal and nine material categories (or regulative ideas in the Kantian sense) which should be a basis of the redefined Polish identity.